Students Learn When Teachers Lead - Basu, Sameena (JOURNAL OF INDIAN EDUCATION, 2014)
The present study examined the relationship between leadership behaviour of teachers and academic achievement at higher secondary level of education. The sample comprised of 480 teachers identified from government higher secondary schools of Kashmir Province. Leadership Behaviour Description Questionnaire having two subscales was administered to collect the data from sample teachers. Statistical techniques like percentage statistics, coefficient of correlation and ANOVA were used to analyse the data. The results showed that majority of the teachers exhibited ineffective initiating structure and consideration leadership behaviour and also showed that leadership behaviour of teachers is significantly related with academic achievement at higher secondary level.